JURIDICAL ANALYSIS OF THE POSITION OF THE DEED OF ESTABLISHMENT OF A LIMITED LIABILITY COMPANY IN RELATION TO THE LEGALITY OF LEGAL ACTIONS OF A SHIPPING COMPANY (CASE STUDY OF PT BIAS DELTA PRATAMA) - Hetti Sitorus; Erniyanti; Titik Aminah; Markus Gunawan; Mania (Journal of International Islamic Law, Human Right and Public Policy, 2026)
The deed of establishment of a limited liability company is an authentic instrument recording the founders’ agreement and the articles of association, while legal-entity status arises upon ministerial approval. In the company’s subsequent development, the deed of establishment must be read together with amendments to the articles of association and deeds recording changes in company data. For PT Bias Delta Pratama, the empirical documents examined include the history of Deed of Establishment Number 183 dated 26 September 1992 and Deed Number 55 dated 28 February 2018, which records the minutes of an Extraordinary General Meeting of Shareholders and is therefore a subsequent corporate deed. This study analyzes the position of that documentary chain in determining the authority of the company’s organs and the binding effect of legal acts performed in the company’s name. This study employs a normative-empirical legal research method using the statute approach, conceptual approach, and empirical approach. The research data consists of primary data obtained through interviews with respondents and informants, as well as secondary data obtained through a literature study of legislation, books, journals, and relevant legal documents. The data are analyzed qualitatively through the processes of reduction, presentation, and conclusion drawing. The results show that the deed of establishment is the documentary basis for forming the company, whereas legal-entity status arises through ministerial approval. After incorporation, representative authority is determined by company law, the articles of association and their amendments, shareholders’ resolutions appointing directors, the recording of changes in company data, and valid powers of attorney. Deed Number 55 of 2018 is not the deed of establishment; it is a deed recording an Extraordinary General Meeting of Shareholders and is used to trace post-incorporation corporate decisions and data. At PT Bias Delta Pratama, internal operational titles do not automatically confer authority to represent the company. Accordingly, amendments to the articles or updates to company data must be made according to the legal nature of each change.